A Design Thinking Technique of Letting Problems Solved by Self. (21st August 2022) - Zhao, Yulin; Luh, Dingbang; Sun, Yue; Sun, Fei
Abstract : This paper puts forward the thinking mode of problems solved by self, which can turn complaints into wishes that resembles needs beyond user's expectation and imagination. Inferring the framework for solving problems from existing problem materials, the proposed technique employs literal logic to manipulate mathematical strategies, so that rational thinking can guide the development of affectional contexts, and automatically generate solution concepts, systematically and systemically. Through the demonstration of a design case study and comparative analysis of the effectiveness of related creative techniques the feasibility, novelty, advancement, and practicality of the proposed model are verified. The proposed tool can assist its users to think outside the black box and create "needs that adopters yet to aware."